Endothelial factors and blood homocysteine level in adolescents with rheumatic diseases - T. O. Holovko; L. F. Bohmat; N. S. Shevchenko; Yu. V. Volkova; L. L. Sukhova; O. S. Pavlova (Сучасні медичні технології)
It is known that the dysfunction of the endothelium has crucial role in many pathological conditions and underlines adverse cardiovascular events.